Експериментальне обґрунтування застосування біодеградіруючих сплавів на основі магнію в динамічному інтрамедулярному остеосинтезі діафізарних переломів великогомілкової кістки - Яцун, Євген Володимирович; Yatsun, E. V. (My University, 2023)
Дисертаційне дослідження присвячене поліпшенню результатів лікування пацієнтів із діафізарними переломами великогомілкової кістки шляхом експериментального та клінічного обґрунтування методики динамічного блокованого інтрамедулярного остеосинтезу з використанням біодеградуючого блокованого гвинта, виготовленого з магнієвого сплаву. Діафізарні переломи кісток гомілки займають провідне місце серед переломів довгих кісток (8,1–36,6 %) У структурі інвалідності їхнє місце становить від 7 до 37,6 % усіх травм опорно-рухової системи. За даними різних авторів, кількість порушень зрощення після переломів великогомілкової кістки досягає 25–40 %. Тривала тимчасова непрацездатність, інвалідність та великі матеріальні витрати на лікування — це основні аспекти з комплексу проблем медико-соціальної реабілітації таких постраждалих. The dissertation research is devoted to the improvement of the results of treatment of patients with diaphyseal fractures of the tibia by experimental and clinical substantiation of the technique of dynamic blocked intramedullary osteosynthesis using a biodegradable blocked screw made of magnesium alloy. Diaphyseal fractures of the tibia occupy a leading place among fractures of long tube bones (8.1-36.6 %). In the structure of disability, their input is 7-37.6 % of all injuries of the musculoskeletal system. According to various authors, the number of impaired consolidations after fractures of the tibia reaches 25-40 %. Prolonged temporary incapacity for work, disability and high material costs for treatment are the main aspects of the complex of problems of medical and social rehabilitation of such patients. Nowadays, there is no doubt about the advantages of surgical methods of treatment of diaphyseal fractures of the tibia over conservative, so their priority is not in doubt. Blocked intramedullary osteosynthesis (BIOS) with metal implants remains one of the most common methods of treating long tube bone fractures. Closed BIOS is now considered the gold standard for the treatment of diaphyseal fractures of the tibia. Its biomechanical features and low invasiveness allow achieving rapid predictable recovery of the function of the injured segment with minimal complications. Stainless steel and titanium alloys are the main materials used to make such implants. They have the necessary mechanical properties and are bioinert materials.
Experimental substantiation of the of biodegradable magnesium alloys use in dynamic intramedullary osteosynthesis of diaphyseal fractures of the tibia
Keywords: великогомілкова кістка; динамічний блокований інтрамедулярний остеосинтез; біодеградуючий гвинт із магнієвого сплаву; tibia; dynamic blocked intramedullary osteosynthesis; biodegradable magnesium alloy screw